2022
DOI: 10.1093/intqhc/mzac071
|View full text |Cite
|
Sign up to set email alerts
|

Israeli COVID lockdowns mildly reduced overall use of preventive health services, but exacerbated some disparities

Abstract: Background During 2020, Israel experienced two COVID-19-related lockdowns that impacted the provision of primary and secondary preventive care. Methods We examined the month-by-month performance of selected preventive care services using data from Israel’s national Quality Indicators in Community Healthcare (QICH) program. Process of care measures included Hemoglobin A1c (HbA1c) testing, cholesterol testing, colon cancer scre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 12 publications
1
3
0
Order By: Relevance
“…We showed that, across all ten centres, monthly HbA1c requests dropped by 81.9–92.1% in April 2020 compared with the mean monthly 2019 request numbers. This replicates our previous findings [ 8 ], those from the US (a reduction of 66% in HbA1c testing during the first 8 weeks of the pandemic) [ 18 ], Israel (a reduction in HbA1c of ~ 55% during April 2020 [ 19 ] and Spain (a reduction of 52% during March–June 2020 in people with a HbA1c of < 48 mmol/mol) [ 20 ]. It is also consistent with other UK findings by Carr et al [ 9 ], which showed a similar magnitude of reduction in HbA1c testing in April 2020.…”
Section: Discussionsupporting
confidence: 90%
“…We showed that, across all ten centres, monthly HbA1c requests dropped by 81.9–92.1% in April 2020 compared with the mean monthly 2019 request numbers. This replicates our previous findings [ 8 ], those from the US (a reduction of 66% in HbA1c testing during the first 8 weeks of the pandemic) [ 18 ], Israel (a reduction in HbA1c of ~ 55% during April 2020 [ 19 ] and Spain (a reduction of 52% during March–June 2020 in people with a HbA1c of < 48 mmol/mol) [ 20 ]. It is also consistent with other UK findings by Carr et al [ 9 ], which showed a similar magnitude of reduction in HbA1c testing in April 2020.…”
Section: Discussionsupporting
confidence: 90%
“…Globally, the COVID-19 pandemic has resulted in a heterogeneous disruption of outpatient care, which can stem from differences in the resilience of national health systems and variable government responses to face the spread of SARS-CoV-2 [1] , [15] , [16] . This could explain the absence of apparent decline in the quality of diabetes care in our setting, while a significant drop in quality was found in other countries [5] , [7] . This hypothesis is corroborated by the results of a recent international survey, which showed that 66.6% of Swiss primary care providers considered that the overall quality of medical care had not been affected by the COVID-19 pandemic, whereas this share ranged from 16.6% to 40.1% in the nine other high-income countries included in the study [17] .…”
Section: Discussionmentioning
confidence: 50%
“…In the field of diabetes care, evidence is equivocal. Some research found that quality indicators like glycaemic control slightly improved during lockdown [4] , while other works reported a decline in the quality of diabetes care [5] , [6] , [7] . Taking advantage of longitudinal data collected in the setting of a Swiss population-based cohort study, this research aimed at comparing the quality of diabetes care before and during the COVID-19 pandemic, as measured by self-reported indicators.…”
Section: Introductionmentioning
confidence: 99%
“…The clinical impact of such a contracted mammography service is reflected in the 44% reduction (247 vs. 139) in new breast cancers diagnosed at a large WCP anatomical pathology laboratory in the first three months of lockdown (1 April to 30 June 2020), compared to the corresponding period in 2019 [31]. Substantial decreases in mammographic investigations are common in all reports on the impact of COVID-19 on radiological departments [32][33][34]. The American Mammography Database recorded a 42% reduction in diagnostic studies during peak COVID lockdown, compared to pre-COVID levels, with a corresponding 52% reduction in breast cancer diagnoses.…”
Section: Discussionmentioning
confidence: 99%